Exploring the scope and applications of anti-doping measures in ultramarathon: an analysis of the positions of ultramarathon race organizers - Jill Colangelo; Alexander Smith; Stefanie Hachen; Michael Liebrenz (Frontiers Media S.A., 2024)
IntroductionWith ultramarathon attracting burgeoning interest, evidence has emerged about doping behaviors. However, currently, research into the anti-doping policy landscape and the adoption of testing and athlete surveillance is limited, including the applicability of rubric from the World Anti-Doping Agency (WADA) and National Anti-Doping Organizations (NADOs). Consequently, it remains unclear if anti-doping provisions have been developed and enforced in ultramarathon, which is a timely consideration given growth in the sport.MethodsThis study gathered perspectives on anti-doping and testing procedures from ultramarathon race organizers (UMROs). To that end, a sample of n = 35 prominent competitions was compiled using web materials and community engagement, encompassing elite and amateur entrants, diverse course designs, and prize money opportunities. Data-gathering was conducted across two phases between November and December 2023, with an initial review of UMRO web resources. Subsequently, UMROs were contacted via email to validate or ascertain their anti-doping and testing policies. Insights from UMRO respondents were reviewed and coded. UMROs who did not reply were excluded from the analysis.ResultsBased on this methodology, the positions of n = 17 UMROs were captured, covering 159 ultramarathon races and approximately 96,500 annual participants. Of these, n = 8 UMROs did not have a self-developed policy and their rubric was pursuant to external authorities like WADA and NADOs. n = 4 had created a specific proprietary policy, which often incorporated WADO or NADO materials. The remaining n = 5 UMROs reported no anti-doping controls were in place at the time of the study. There was also notable heterogeneity in testing and surveillance, ranging from rigorous procedures to an absence of protocols. Interestingly, none of the included UMROs explicitly reported that they had enacted anti-doping measures against athletes.DiscussionVarious determinants could inform these regulatory inconsistencies across UMROs, such as financial constraints, infrastructural and logistical barriers, cultural factors, and the lack of a unifying international federation in ultramarathon. Given the disparate approaches identified in our results, greater cooperation and education may be necessary to enhance understanding about the implications of doping and advance cohesive frameworks. This should involve collaborations with WADA and NADOs to promote best-practices and evidence-based exchanges within the community.